Rational Action in the Sociology of Max Weber and in the Rational Choice Theory - Norkus, Zenonas (Problemos, 2000)
The article discusses the relations between the concepts of rational action in Weber’s sociology and rational choice theory. The task of the article is a limited one because no consideration is given to Weber’s ruminations on the rationality vs. irrationality as an attribute of institutions (social systems) and that of systems of meaning (culture). The article discusses the work of R. Boudon designing the “cognitivist” model of rational choice, the proposal of J. Elster to analyse value-oriented behaviour in terms of lexicographic preferences and the recent work of M. Baurmann which substructs Weber’s dichotomy of instrumental rational vs. value rational action with the more differentiated classification of the rational action including two types of instrumental rational action (situation-maximizing and disposition-maximizing). The upshot of the discussion are the following statemens. (1) M. Weber anticipates in his concept of the subjectively rational instrumental action the transformation of the marginal utility theory (treated by M. Weber as the theory of the “strictly” rational action) into the theory of the subjective expected utility. (2) M. Weber’s concept of the interpretive sociology anticipates the versions of the rational choice approach classified by D. P. Green and I. Shapiro as “segmented” and “partial universalism”. (3) Weber’s instrumental rational action and value rational action are the kinds of the general concept of the individual practical rationality which designates the behaviour consistent with regard to socially shared beliefs. (4) Weber’s strictly value rational action is not identical with the norm-conform behaviour of the “homo sociologicus”. (5) Weber’s concept of rational action contains the conceptual resources allowing for the substruction to Weber’s dichotomy of value vs. instrumental action with the more differentiated classification of the forms of rational action which can be used for the elaboration of the Weber’s characteristic of the modernity.